EFEKTIVITAS PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN DALAM MEMBERDAYAAN MASYARAKAT MISKIN - Yulpia Winingsih; Sarwan Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This article aims to uncover and analyze the achievement of objectives, accuracy of objectives, satisfaction, and success of rural agribusiness development programs in empowering the poor in the Pesisir Selatan, West Sumatera. This is a qualitative descriptive research type. A few poor communities are respondents of this research. Interview, observation and documentation use as data collection techniques. The results showed that the rural agribusiness development program has not been able to help the community as a whole because there are combinations of farmer groups that have been effective and there is a combination of farmer groups that have not been effective. Effective farmer group combinations are evidenced by increasing income, group members, and assets. While the combination of farmer groups that have not been effective is marked by community mentality that is difficult to change bad habit in using money for ineffective purposes. It is concluded that rural agribusiness development programs has not been succeed in empowering Pesisir Selatan community. The implication is poor community should be given more intensive community empowerment by government through more effective strategies.